Alumina-Activated Carbon Composite as Adsorbent of Procion Red Dye from Wastewater Songket Industry - Poedji Loekitowati Hariani; Fatma Fatma; Zulfikar Zulfikar (The Journal of Pure and Applied Chemistry Research, 2015)
Alumina-activated carbon composite has been synthesized and studied for adsorption procion red dye. Composite was prepared by precipitation method aluminium hydroxide on the surface of activated carbon followed by calcinations. The Fourier transform Infra Red (FTIR), Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDS) and Brunaeur Emmet Teller (BET) surface are being used to characterize the adsorbent. Batch adsorption experiments were carried out for the adsorption of procion red dye. Effect of the mass of composite, stirrer speed, contact times and pH of the solution on the adsorption capacity were studied. The obtained optimum conditions applied to adsorp of procion red dye from wastewater songket industry. The result showed that the adsorption optimum at mass of alumina-activated carbon composite 0.1 g, stirrer speed 150 rpm, contact times 2 hours at pH of the solution 9. The adsorption isotherm data according to Langmuir isotherm. The alumina-activated carbon composite can be removal of procion red dye from wastewater songket industry with effectiveness adsorption of 88.21 %.